Effect of Growth Regulators on Growth and Quality of Strawberry cv. Sweet Sensation Grown in Pot Culture - Panda, D.; Mondal, S. (International Journal of Bio-resource and Stress Management, 2023)
A pot culture experiment was conducted at Institute of Agriculture, Visva-Bharati, Sriniketan, West Bengal, India during the rabi season (October, 2018–March, 2019) to study the effect of growth regulators such as 28-Homobrassinolide and Triacontanol on growth and yield of strawberry cv. Sweet Sensation. The treatments consisted of seven levels of growth regulators including control viz. control, 0.5 ppm, 1 ppm and 2 ppm of 28-Homobrassinolide and 2ppm, 5 ppm and 10 ppm of Triacontanol. The effect of growth regulators was studied on different morpho-physiological parameters and biochemical and quality parameters such as chlorophyll content of leaves, ascorbic acid, titratable acidity and TSS of fruit. The results revealed that the foliar application of 0.5 ppm of 28-Homobrassinolide produced the maximum plant height, number of leaves plant-1, petiole length, canopy spread, leaf area plant-1, crown diameter, shoot dry weight and root dry weight, RWC, number of flowers plant-1, number of fruits plant-1, percent fruit set, fruit length and fruit diameter, chlorophyll content of leaves, whereas the treatment of 1 ppm of 28-Homobrassinolide recorded maximum plant height, petiole length. However, the minimum value of the morphological, biochemical, yield and quality parameters were recorded in control (foliar spray of water). Hence form present study it may be confirmed that foliar application of 28-Homobrassinolide @ 0.5 ppm and 1 ppm significantly improved the growth, yield, and quality attributes of strawberry.